GRAVITATION EQUALITY AS BASIS OF THE STATE’S ECONOMIC DEVELOPMENT ALGORITHM IN THE CONTEXT OF FORMING OF THE INDEPENDENT BALANCED ECONOMIC POLICY - Nikitina Marina; Sviridov Oleg; Lunyakov Oleg Vladimirovich; Naumenko Roman; Mirankov Dmitry; Niyazbekova Shakizada; Soldatov Maxim (Scientific Journal of Pedagogy and Economics, 2021)
This article presents an algorithm of economic development of state, focused on finding the optimal direction of foreign economic activity in the context of ensuring economic security of region. The developed mechanism makes it possible to take into account the gravitational affiliation of states on the basis of the created integral indicator of the strength of economic gravity. Based on a theoretical assessment of the variability of the paths of economic development, a conclusion is made about the effectiveness of bilateralism in the context of global economic instability. In the process of building macroeconomic policy, the state assesses the bilateral and multilateral aspects of economic activity. The multifactorial nature of economic activity forms the multitasking of country's economic development. Accordingly, solving economic problems requires a systematic approach. The main stages of the algorithm for choosing the path of economic development of the state: 1. Choosing a direction of economy optimization. 2. Assessment of the foreign policy position of the state, on the basis of which the choice of bilateral or international path is made. 3. Evaluation of bilateral optimization in accordance with the state of the economy. Bilateral optimization is carried out depending on the economic gravity of states, which determines the type of interaction of elements. When assessing the current level of bilateral economic relations and the formation of prospects for cooperation, it is necessary to use the index of economic gravity of countries, which takes into account a level of trade gravity of countries, an indicator of distance dependence between countries, a measure of political calm and an indicator of monetary and financial proximity of countries. The developed mechanism of economic actions of the state provides for the existence of an economic and political choice of the vector of economic development, taking into account the state national strategy. Reflecting systemic inversely proportional relationship between the rate of economic growth and country's economic sovereignty, the algorithm is focused on overcoming systemic interstate imbalances in the world economy.